Gender Equality Messages in Film Marlina The Murderer In Four Acts - Husen Mulachela; Aurelius RL Teluma; Eka Putri Paramita (JCommsci - Journal Of Media and Communication Science, 2019)
This research trying to analyze the meaning of symbols in the film Marlina The Murderer in Four Acts based on the indicators of gender equality namely, access, participation, control, and benefits. The unit of analysis in this study includes the audio and visual elements that exist in a selected scene for later analysis using the Roland Barthes semiotic method known as the "two order of signification" to find the meaning of denotation and connotation meanings and myths contained in both order systems. The whole series in this study refers to the framework of thinking with the aim of answering the formulation of the problem in research. From the results of the study, researchers found as many as 17 scenes containing the message of gender equality by including indicators of gender equality both in audio and visual elements. After going through the scene analysis process using the Roland Barthes semiotics method, control indicators in gender equality are found more prominently in films, then followed by indicators of access, participation, and benefits. This shows how the important role of control indicators in gender equality is applied so that other indicators can work.Keywords: Semiotic; film; gender equality; Marlina the Murderer in Four Acts